Attenuated Joint Tissue Damage Associated With Improved Synovial Lymphatic Function Following Treatment With Bortezomib in a Mouse Model of Experimental Posttraumatic Osteoarthritis. Issue 2 (5th January 2019) - Wang, Wensheng; Lin, Xi; Xu, Hao; Sun, Wen; Bouta, Echoe M.; Zuscik, Michael J.; Chen, Di; Schwarz, Edward M.; Xing, Lianping
Abstract : Objective: To investigate the roles of the synovial lymphatic system in the severity and progression of joint tissue damage and functional responses of synovial lymphatic endothelial cells (LECs) to macrophage subsets, and to evaluate the therapeutic potential of the proteasome inhibitor bortezomib (BTZ) in a mouse model of experimental posttraumatic osteoarthritis (OA). Methods: C57BL/6J wild‐type mice received a meniscal ligamentous injury to induce posttraumatic knee OA. Lymphangiogenesis was blocked by a vascular endothelial growth factor receptor 3 (VEGFR‐3) neutralizing antibody. Synovial lymphatic drainage was examined by near‐infrared imaging. Joint damage was assessed by histology. RNA‐sequencing and pathway analyses were applied to synovial LECs. Macrophage subsets in the mouse synovium were identified by flow cytometry and immunofluorescence staining. M1 and M2 macrophages were induced from mouse bone marrow cells, and their effects on LECs were examined in cocultures in the presence or absence of BTZ. The effects of BTZ on joint damage, LEC inflammation, and synovial lymphatic drainage were examined. Results: Injection of a VEGFR‐3 neutralizing antibody into the joints of mice with posttraumatic knee OA reduced synovial lymphatic drainage and accelerated joint tissue damage. Synovial LECs from the mouse OA joints had dysregulated inflammatory pathways and expressed high levels of inflammatory genes. The number of M1 macrophages was increased in the knee joints of mice with posttraumatic OA, thereby promoting the expression of inflammatory genes by LECs; this effect was blocked by BTZ. Treatment with BTZ decreased cartilage loss, reduced the expression of inflammatory genes by LECs, and improved lymphatic drainage in the knee joints of mice with posttraumatic OA. Conclusion: Experimental posttraumatic knee OA is associated with decreased synovial lymphatic drainage, increased numbers of M1 macrophages, and enhanced inflammatory gene expression by LECs, all of which was improved by treatment with BTZ. Intraarticular administration of BTZ may represent a new therapy for the restoration of synovial lymphatic function in subjects with posttraumatic knee OA.